Protection of AC and DC distribution systems Embedding distributed energy resources: A comparative review and analysis. (November 2015) - Monadi, Mehdi; Amin Zamani, M.; Ignacio Candela, Jose; Luna, Alvaro; Rodriguez, Pedro
Abstract: The integration of distributed generation (DG) units into distribution networks has challenged the operating principles of traditional AC distribution systems, and also motivated the development of emerging DC systems. Of particular concern are the challenges associated with the operation of conventional protection schemes and/or devices. This paper first analyses the fault current characteristics in AC and DC distribution systems; it then presents a comprehensive review of the latest protection methods proposed for distribution systems embedding DGs. In addition, the advantages and disadvantages of each method are outlined and compared. The differences between the protection algorithms employed in/proposed for AC and DC systems are also discussed. Finally, this study identifies the future trends and provides recommendation for researches in the field of protections of DC distribution networks.